1994
DOI: 10.1128/jvi.68.3.1843-1853.1994
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete protection, but suppression of virus burden, elicited by subunit simian immunodeficiency virus vaccines

Abstract: We compared the efficacy of immunization with either simian immunodeficiency virus (SIV) Env glycoprotein (Env), Env plus Gag proteins (Gag-Env), or whole inactivated virus (WIV), with or without recombinant live vaccinia vector (VV) priming, in protecting 23 rhesus macaques (six vaccine and two control groups) from challenge with SIVmac251 clone BK28. Vaccination elicited high titers of syncytium-inhibiting and anti-Env (gp120/gpl60) antibodies in all vaccinated macaques and anti-Gag (p27) antibodies in group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 33 publications
1
24
2
Order By: Relevance
“…Previous studies have shown that certain lentivirus-vaccinated hosts, although not fully protected, may nevertheless experience attenuated infections following challenge, as shown by reduced viral loads or delayed disease progression (1,17,18,22,26,31,46). In our study, there was little evidence that the initial p.v.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have shown that certain lentivirus-vaccinated hosts, although not fully protected, may nevertheless experience attenuated infections following challenge, as shown by reduced viral loads or delayed disease progression (1,17,18,22,26,31,46). In our study, there was little evidence that the initial p.v.…”
Section: Discussioncontrasting
confidence: 67%
“…However, these strategies have, in general, given disappointing results in primate protection studies. Immunization with regimens that include recombinant vaccinia virus or Mycobacterium bovis BCG constructs has not protected macaques against challenge with most simian immunodeficiency virus (SIV) isolates (1,4,(7)(8)(9)24). Novel vaccine strategies capable of eliciting HIV-1specific CTL should, therefore, be pursued.…”
mentioning
confidence: 99%
“…It is in the light of this that attempts to vaccinate against agents such as EBV, which become latent or establish persistence, should be viewed [Spring et al, 1996]. Successful vaccination against experimental lentivirus infection of primates has been reported in terms of delayed disease [Sutjipto et al, 1990], or by a gradient of suppression of growth of the challenge virus from sterilizing immunity to a decrease in virus or provirus burden [Israel et al, 1994]. In the context of primary infection with EBV, a decrease in virus replication following immunization may well prevent infectious mononucleosis in adolescence, and act to decrease the severity of disease in the EBV-negative recipients of a positive transplant.…”
Section: Discussionmentioning
confidence: 99%